Auditing the Sustainability Reports – Challenges and Perspectives - Ovidiu-Constantin BUNGET; Alin-Constantin DUMITRESCU; Oana BEZERGHEANU; Oana BOGDAN; Valentin BURCA (Audit Financiar)
This paper analyzes the most recent sustainability reports of Romania’s largest companies listed on the Bucharest Stock Exchange (BVB), using NVivo to examine ESG-related keywords across sectors. The results highlight strong emphasis on governance and environmental themes, especially within the banking, technology, energy, and materials industries. In contrast, the healthcare and food & beverage sectors show comparatively lower sustainability engagement. While most companies demonstrate alignment with established frameworks, the depth and structure of disclosures vary. Despite the growing importance of audit and assurance under the CSRD, explicit references to these elements remain limited. This study offers a current snapshot of sustainability reporting practices in Romania, providing a reference point for comparative analysis with forthcoming disclosures.